Green Chemistry: Principles and Case Studies. By Felicia A. Etzkorn. Issue 2 (8th December 2020) - Sheldon, Roger A.
Abstract : Royal Society of Chemistry, Cambridge 2020. 447 pp., softcover, € 78.00.—ISBN 978‐1‐78801‐798‐5